Digging into the ʿUbaid period bitumen from Dosariyah - Van de Velde, Thomas (Proceedings of the Seminar for Arabian Studies, 2015)
The recent excavations at Dosariyah yielded a large collection of bitumen artefacts, of which twenty samples were selected for analysis to determine their geological origin. Stable carbon isotope analysis on the asphaltene fraction and gas chromatographymass spectrometry (GC-MS) analysis on the saturated hydrocarbons were the analytical techniques used in this research. It was possible successfully to determine the origin of eighteen samples, which all came from a bitumen seepage in northern Iraq. The results of this current research are compared with similar studies on bitumen. This paper offers an in-depth review of the available material on bitumen origins and trade during the time in which Dosariyah was inhabited, and discusses other relevant periods. As the bitumen used in Dosariyah came from Mesopotamia, this paper also examines the bitumen material for that region, especially in regard to the mechanisms of trade and contact with settlements in the Gulf. In general, findings from this research conducted on the bitumen from Dosariyah are in concordance with the results from similar bitumen analyses conducted on Mesopotamian samples. These analyses lead to the conclusion that c Ubaid 3 period bitumen from northern Iraq was being used in both Mesopotamia and the Gulf. This, however, raises some questions on how to interpret the bitumen found at as-Sabiyah. In conclusion, there are also some pitfalls and problems regarding the bitumen trade and the available material on which such hypotheses may be based.